Stability and Collective Rationality - Lensberg, Terje (Econometrica, 1987)
A collective choice problem involves a set of agents and a set of feasi ble utility vectors. Many solutions to the collective choice problem (e.g., the Nash solution) are collectively rational, i.e., consistent with the maximization of some ordering of utility space. In this pap er, a stability condition due to J. C. Harsanyi is used to obtain the following integrability result: any solution satisfying Pareto optim ality, continuity, and bilateral stability can be represented by an a dditively separable Bergson-Samuelson social welfare function. Copyright 1987 by The Econometric Society.